Andean Spanish in the province of Huamanga: districts of Quinua and Pacaycasa - Ruiz Villa, Julissa Milagros (2020)
In this paper, the morphological and syntactic analysis of the Andean Spanish variety, specifically, from the districts of Quinua and Pacaycasa, which are located in the province of Huamanga, Ayacucho. In this way, this research is methodologically descriptive and explanatory, since a series of examples corresponding to the diverse grammatical processes obtained have been noted. Furthermore, a brief description will be included which contrasts with other authors who deal with the aforementioned topics.